P.003 CJD in the modern era: The value of clinical features and diagnostic tests. (June 2022) - Shir, D; Lazar, EB; Graff-Radford, J; Aksamit, AJ; Cutsforth-Gregory, JK; Jones, DT; Botha, H; Ramanan, VK; Prusinski, CC; Porter, AL; Day, GS
Abstract : Background: The advent of real-time quaking-induced conversion (RT-QuIC) assays has transformed the diagnostic approach to sporadic Creutzfeldt-Jakob disease (CJD) facilitating earlier recognition of affected patients. Recognizing this, we evaluated the performance of clinical features and diagnostic tests for CJD in the modern era. Methods: Clinical data were extracted from the electronic medical records of 115 patients with probable or definite CJD assessed at Mayo Clinic from 2014-2021. Clinical features and diagnostic tests were evaluated at presentation, and associations with diagnosis and prognosis determined. Results: Mean age-at-symptom onset was 64.8±9.4 years; 68 patients were female (59%). The sensitivity of clinical markers (myoclonus) and tests historically considered in patients with suspected CJD was poor (stereotyped EEG abnormalities, 16%; CSF 14-3-3, 60%). Conversely, RT-QuIC (93%), t-tau >1149 pg/mL (88%), and characteristic signal abnormalities on MRI (77%) identified most patients. Multivariable linear regression confirmed shorter days-to-death in patients with myoclonus (125.9, CI95% 23.3-15.5, p=0.026), visual/cerebellar signs (180.19, CI95% 282.2-78.2, p<0.001), positive 14-3-3 (193, CI95% 304.9-82.9; p<0.001), and elevated t-tau (9.0, CI95% 1.0-18.0, for every 1000 pg/ml elevation; p=0.041). Conclusions: CSF RT-QuIC and elevated t-tau, and stereotyped MRI abnormalities were consistently detected in CJD patients. Myoclonus, EEG findings, and CSF protein 14-3-3 were less useful in the modern era.